Membrane lipid rafts are required for AMPA receptor tyrosine phosphorylation - Hayashi, Takashi (Frontiers in Synaptic Neuroscience, 2022)
Membrane lipid rafts are sphingolipids and cholesterol-enriched membrane microdomains, which form a center for the interaction or assembly of palmitoylated signaling molecules, including Src family non-receptor type protein tyrosine kinases. Lipid rafts abundantly exist in neurons and function in the maintenance of synapses. Excitatory synaptic strength is largely controlled by the surface expression of α-amino-3-hydroxy-5-methyl-4-isoxazole propionate (AMPA) receptors in the mammalian brain. AMPA receptor endocytosis from the synaptic surface is regulated by phosphorylation of the GluA2 subunit at tyrosine 876 by Src family kinases. Here, I revealed that tyrosine phosphorylated GluA2 is concentrated in the lipid rafts fraction. Furthermore, stimulation-induced upregulation of GluA2 tyrosine phosphorylation is disrupted by the treatment of neurons with a cholesterol-depleting compound, filipin III. These results indicate the importance of lipid rafts as enzymatic reactive sites for AMPA receptor tyrosine phosphorylation and subsequent AMPA receptor internalization from the synaptic surface.